A COMPARATIVE STUDY OF PRIMARY 1 STUDENTS’ ATTITUDES TOWARD AND ACHIEVEMENT IN CHINESE LANGUAGE CLASS UNDER GAME TEACHING METHOD AND TRADITIONAL TEACHING METHOD AT AN INTERNATIONAL SCHOOL IN THAILAND - PENG, CHENG; RAFAEL GONZALEZ GONZALEZ, ORLANDO (Scholar: Human Sciences, 2022)
The purpose of this paper was to determine if there were significant differences in the attitude toward and the achievement in Chinese language class between two classes of Primary 1 students, one learning under the game teaching method and the other learning under the traditional teaching method, at an international school in Thailand during the academic year 2020-2021. This study was conducted on a convenience sample of 49 Primary 1 students, whose attitude toward and achievement in Chinese language class was measured before and after an experimental period of three weeks, during which the experimental group (24 students) was taught through the game teaching method, and the control group (25 students) was taught through the traditional teaching method. A 10-item questionnaire, based on the “attitude toward the learning situation” subscale from the Attitude/Motivation Test Battery (AMTB; Gardner, 2006), was used for measuring participants’ level of attitude toward Chinese language class, while a 35-question test was administered as pre- and post-test to measure participants’ achievement in Chinese language class. The collected data were analyzed using descriptive statistics (means, standard deviations, frequencies, and percentages) and independent samples t-tests. The findings showed that students in the experimental group had a significantly higher attitude toward Chinese language class than students in the control group. However, no significant difference in the gain in achievement in Chinese language class was seen between the experimental and control groups.